Persepsi Mahasiswa terhadap Kinerja BEM dalam Melakukan Koordinasi Ormawa Selingkungan UNP - Wahib Assyahri; M. Fachri Adnan; Adil Mubarak (Faculty of Social Science, Universitas Negeri Padang, 2018)
BEM (Student Executive Organization) was basically a campus executive institution that has a function to coordinate all student activities in the university environment through student organizations. However, the coordination that was carried out by BEM UNP with the student organizations within UNP for period for of 2016-2017 was not effective. The BEM and the student organizations’ work program went on singly without supporting and cooperating. The synergy among the student organizations has not yet reached. This study aims to analyze students’ perceptions of BEM UNP performance in coordinating with the student organizations in UNP for period of 2016-2017. This study used descriptive quantitative method. The sample in this study were 100 students in UNP determined with Slovin formula and Proportionate Stratified Random Sampling technique. Data were collected through questionnaires with Likert scale measurements and interviews. The finding of this study showed that the students’ perceptions about the coordination of BEM UNP with the students organizations in UNP for period of 2016-2017 were in the medium category with the mean of 2.68. Based on this result, BEM UNP needs more efforts to build up the communication and maintain the coordination with the student organizations, so that the synergy among the student organizations could be realized well